Instagram Notes Sebagai Media Ekspresi Di Kalangan Mahasiswa Universitas Trunojoyo Madura - Nabila Firdaus Irsyadillah; Adelia Kurniawati; Putri Eka Lestari; Aruni Anggita Nur Azizah; Eka Dwi Saraswati; Sri Wahyuningsih (Journal of Innovative and Creativity, 2026)
The development of micro features on social media has introduced new forms of self expression that have not been widely studied in depth, one of which is Instagram Notes. This study aims to understand how students interpret and use Instagram Notes as a space for self expression in their digital lives. The study employed a qualitative approach with phenomenological methods, involving students as purposively selected participants. Data were collected through in depth interviews and analyzed thematically to uncover patterns of experience and meaning in using the feature. The results indicate that Instagram Notes is used as a personal, ephemeral, and non performative space for expression, primarily for channeling emotions and self reflection without the need for visual representation or an orientation toward audience response. These findings confirm that Instagram Notes functions as a space for intrapersonal expression within the digital public sphere, thus broadening the understanding of self expression practices and emotion regulation in contemporary digital communication studies.